A1 3 Chaos of Meteorology - Tasyaka, Andrea; Bujdoso, Kieran; Stentiford, Madeleine; Holmes, Pippa (Physics Special Topics, 2024)
In this paper, we investigated the effects of the initial parameters of a system being altered and the resulting behaviour of the Lorenz system; a scientific model in chaos theory. The simulation was performed using two values of σ, 5.06 and 0.506, with fixed values of β = 8 3 and ρ = 28. The subsequent graphs show the difference in σ, with the larger value showing more chaotic characteristics; having pronounced oscillations and repeated loops spiralling, whilst the smaller value followed a simple, predictable path. These results proved that a small change can have an enormous effect in a chaotic system.